Glioblastoma multiforme versus pleomorphic xanthoastrocytoma with anaplastic features in the pathological diagnosis: a case report. Issue 1 (December 2016) - Yamada, Shoko; Murakami, Hideki; Tomita, Yusuke; Nakane, Makoto; Shibui, Soichiro; Takahashi, Mikiko; Kawamoto, Masashi
Abstract Background Pleomorphic xanthoastrocytoma (PXA) with anaplastic features should be strictly distinguished from glioblastoma multiforme (GBM). Case presentation A case of PXA that was initially diagnosed as GBM is presented. A 42-year-old man visited our clinic because of right hemiparesis and total aphasia. Head magnetic resonance imaging demonstrated enhanced multiple cystic lesions in the left temporal lobe suggesting an intra-parenchymal brain tumor. The lesion was partially removed and GBM with a Ki-67 index of 20 % was diagnosed by pathological examination of the resected specimen. Despite receiving radiation and chemotherapy, the patient died 6 months after the first admission. At autopsy, the boundary between the tumor and normal brain tissue was clear. Large parts of the tumor demonstrated typical features of PXA, including pleomorphism, clear xanthomatous cells with foamy cytoplasm, positive silver staining, and a Ki-67 index of less than 1 %. Discussion and conclusions GBM should be diagnosed only when the majority of the tumor cells are undifferentiated. Although the operative specimen appeared typical GBM histologically, the diagnosis of GBM was subsequently excluded by the autopsy finding that much of the tumor had the characteristic features of a benign PXA. Therefore, the final diagnosis in this case was PXA with anaplastic features. PXA with anaplastic features should be carefully distinguished from GBM to facilitate appropriate decisions concerning treatment.